Resource Allocation Strategy for Power Safety Tools with Fuzzy Systems and Edge Computing - Liu, Bin; Luo, Zhongqiang; Dai, Xiang; Chen, Hongbo (Journal of Vibration Testing and System Dynamics, 2026)
As a solution to solve data congestion and improve the quality of service, edge computing emphasizes that the data of local data sources should be processed according to their locations. In order to solve the problem that the efficiency of traditional power safety management tools is low in the management cycle process that affects business delivery, this paper proposes a resource offloading algorithm with multi-access edge computing (MEC) server as the core and cloud collaborative work. Firstly, the application of MEC in the scenario of new infrastructure power safety tools is studied.Then, a three-layer edge computing architecture of terminal, edge and cloud is constructed with resource scheduling, and the attributes of incoming tasks, network transmission and computing resource performance in this scenario are dynamically considered. Finally, the fuzzy logic coordinator is used to determine which services are cached at the edge and which tasks are executed in the cloud. The simulation experiment results show that the superiority of the proposed resource offloading algorithm in the service performance of power safety tools is verified from multiple performance indexes such as service time, task failure rate, and resource utilization rate.